Predicting obesity rate and obesity-related healthcare costs using data analytics. Issue 2 (June 2017) - Revels, Stephanie; Kumar, Sathish A.P.; Ben-Assuli, Ofir
Abstract: Objective: Obesity is a worldwide problem that has been linked to serious medical issues. Obesity-related conditions drain healthcare expenditures globally, and in particular in the U.S. This article suggests methods to forecast future costs associated with obesity-related healthcare in the next two decades. Methods: An Auto Regressive Integrated Moving Average (ARIMA) time series analysis was implemented to model the data published by the Center for Disease Control and Prevention. Results: The findings suggest that the proportion of individuals in the population defined as overweight will decline slowly in the next 20 years. However, the proportion of the population considered obese will increase substantially and could represent as much as 45% of the entire population by 2035. The proportion of morbidly obese will also increase considerably. These trends are likely to impact the actual costs of healthcare considerably. Conclusions: Policy makers in the healthcare sector should be aware of this trend and prepare to deal with increasing numbers of medical problems related to obesity. Concrete recommendations for policy makers are put forward in the discussion as well as avenues for future research. Highlights: Obesity is a worldwide problem which causes a lot of serious medical problems. Obesity affects the healthcare expenditures worldwide and especially for the U.S. Obesity will be increased, about 45% out of the whole population by 2035. The proportion of morbid obese and the actual costs on healthcare will be increased. Implementation of our recommendations can help in the fight against obesity.